Mulher negra quilombola do Vão de Almas: ancestralidade e resistência - Rodrigues Neta, Aurelina Marinho (2021)
This work aims to understand the Kalunga quilombola woman in her experiences, the sens-es and meanings of this Kalunga Being. For that, we used the semi-structured interview and the field notebook, we assumed the historical-dialectical materialism as a methodologi-cal analysis tool, unveiling: (1) the crossings that pervade being a woman; (2) the materi-ality of living conditions being processed in intersectionality: gender, race/racism, machis-mo, prejudice and exploitation of black female bodies/lives. The first chapter of this work is divided into three parts. The first of them addresses racism and its ways of operating, based on the myth of racial democracy and using justifications such as the inferiority of the black population, and the non-existence of racism. In the second part, we present the con-cept of quilombo and the understandings about it, reaffirming it as a space of resistance. In the third part, we present the Chapada dos Veadeiros region and its formation, with an emphasis on the Kalunga population of Vão de Almas, the specificities of the territory and the meanings it takes. In the second chapter, we will fray the gender discussion highlight-ing the existence of feminisms, recognizing the advances of white feminism, and stressing that this is not unique, it has not recognized the situation of black women and does not truly include them in its agendas, since differed in some matters from white females. We will then present black feminism as a possibility to think about black women's issues, and we present African Women'sism as a possible proposal, which seemed to respond best to us in relation to this study, regarding the centrality of the feminine. In the third chapter, we will deal specifically with the quilombola woman of the “Vão de Almas”, based on her narratives, and on the crossings that pervade her human existence: the ruptures to which they were exposed; violence, resistance, machismo, and exploitation, thus reaching the meanings of being a Kalunga quilombola woman for them.